Something in the bone: stories - Greenlee, Benjamin Mace, author; Altschul, Andrew, advisor; Candelaria Fletcher, Harrison, committee member; Bunn, David, committee member (Colorado State University. Libraries, 2019)
A collection of eight fictional stories exploring what it means to be human in an often inhumane world. Written in a variety of points-of-view and styles, these stories examine relationships, gender, violence, the environment, and self-hood, all in an effort to offer solace for the negative emotions we all feel.